Detecting macular edema through optical coherence tomography images Segmentation based on Watershed algorithm - et. al., Anjali Shelkikar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, Optical Coherence Tomography is used to imaging DME image cells in order to assess their properties and calculate their consistency. Firstly, the median filter and morphological operations were used in the experiment. This approach improves image quality and resolves OCT image problems. For statistical analysis, the dataset is used. The DME images were automatically segmented.